The metabolic dynamics of cartilage explants over a long-term culture period - E.K Moo; N.A Abu Osman; B. Pingguan-Murphy (Clinics, 2011)
INTRODUCTION: Although previous studies have been performed on cartilage explant cultures, the generalized dynamics of cartilage metabolism after extraction from the host are still poorly understood due to differences in the experimental setups across studies, which in turn prevent building a complete picture. METHODS: In this study, we investigated the response of cartilage to the trauma sustained during extraction and determined the time needed for the cartilage to stabilize. Explants were extracted aseptically from bovine metacarpal-phalangeal joints and cultured for up to 17 days. RESULTS: The cell viability, cell number, proteoglycan content, and collagen content of the harvested explants were analyzed at 0, 2, 10, and 17 days after explantation. A high percentage of the cartilage explants were found to be viable. The cell density initially increased significantly but stabilized after two days. The proteoglycan content decreased gradually over time, but it did not decrease to a significant level due to leakage through the distorted peripheral collagen network and into the bathing medium. The collagen content remained stable for most of the culture period until it dropped abruptly on day 17. CONCLUSION: Overall, the tested cartilage explants were sustainable over long-term culture. They were most stable from day 2 to day 10. The degradation of the collagen on day 17 did not reach diseased levels, but it indicated the potential of the cultures to develop into degenerated cartilage. These findings have implications for the application of cartilage explants in pathophysiological fields.